Demand-driven Approaches Through Community-based Program to Reduce Open Defecation Behaviors in Two Subvillages of Sukajaya Village in Bogor, West Java, Indonesia - Rafitha, H; Izzatunnisa, U; Pramudito, B; Yunesvi, R; Indah Permatasari, A; Noviani, N; Aprilia, R; Ula, M; Anggun Dimarsetio, K (KnE Life Sciences, 2019)
One significant sanitation problem in Indonesia is the high number of individuals practicing open defecation. The village of Sukajaya, located in the Jonggol district of Bogor in West Java, Indonesia, has poor sanitation practices, with only 40% of the population having toilets. A community-based sanitation program is an approach used to change individual hygiene and sanitation habits by involving the entire community. The aim of this study was to determine the effects of demand-driven approach in a community-based sanitation program to improve residents’ knowledge and behavior change regarding open defecation. This study used both quantitative and qualitative approaches. The quantitative approach consisted of a quasi-experimental design used to determine the progress of the residents’ understanding and habits related to defecation. This study included 42 households from the Iringowo and Cigaruguy subvillages of Sukajaya. A qualitative approach was used to explore the community’s needs, beliefs, attitudes, and culture, and the data was collected through focus group discussions in both sub-villages. The results of the quantitative research, analyzed with Wilcoxon signed-rank test, showed that mean of the residents’ knowledge about open defecation free was 4.14 (range 1–7) on pretest and increased into 9.88 (range 6–12) after intervention, with p values (0.001) < α. The mean of healthy defecation practices scores was 2.79 (range 1–5) on the pretest and 4.52 (range 2–7) after the program, with p values (0.001) < α. The results of the qualitative analysis indicated that the residents had increased knowledge of proper defecation habits. Regarding their habits, the residents began adapting the practice of defecating in toilets. In conclusion, demand-driven approach in community-based sanitation programs is quite effective to increase the residents’ knowledge and practice about proper defecation practices. Keywords: community-based sanitation program, open defecation, sanitation